2012
DOI: 10.2215/cjn.05870611
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of the Effects of Aliskiren in the Renal Versus Systemic Circulation

Abstract: SummaryBackground and objectives Renal hemodynamic effects of inhibitors of the renin-angiotensin system can increase the risk of acute kidney injury under certain conditions. The BP-lowering effects of the renin inhibitor aliskiren are sustained 3-4 weeks after withdrawal. In this study, the reversibility of the renal hemodynamic effects of aliskiren was tested. Design, setting, participants, & measurementsIn this open-label study, renal perfusion was measured by 1.5-T magnetic resonance imaging-arterial spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Therefore, repeated measurements can be obtained without dye-related risks to the patient. Previously, we compared MRI-ASL with para-aminohippuric acid plasma clearance (the gold standard of renal perfusion measurements) and found a close relationship (r=0.58; P,0.001), indicating that this technique can approximate kidney perfusion (3,4).…”
Section: Introductionmentioning
confidence: 81%
“…Therefore, repeated measurements can be obtained without dye-related risks to the patient. Previously, we compared MRI-ASL with para-aminohippuric acid plasma clearance (the gold standard of renal perfusion measurements) and found a close relationship (r=0.58; P,0.001), indicating that this technique can approximate kidney perfusion (3,4).…”
Section: Introductionmentioning
confidence: 81%
“… 21 Another study demonstrated a significant increase in renal perfusion quantified with ASL, using the renin inhibitor aliskiren. 39 The same group has shown that renal denervation performed in patients with drug-resistant hypertension does not appear to impact renal perfusion, again assessed with ASL. 40 These data suggest that ASL is a promising method for the assessment of renal hemodynamic changes during therapeutic interventions, without the need for more time-consuming methods, the administration of exogenous contrast agents or the use or ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of a variety of drugs on renal perfusion have been assessed with ASL. For example, RBF has been shown to increase during aliskiren therapy and return to original levels after withdrawal of the drug [ 36 ]. Others include telmisartan [ 28 ], furosemide [ 37 ], losartan [ 53 ] and captopril [ 54 ].…”
Section: Recent Developments In Renal Aslmentioning
confidence: 99%